Expression of cancer-associated genes in prostate tumors - Rosenberg, E.E.; Gerashchenko, G.V.; Hryshchenko, N.V.; Mevs, L.V.; Nekrasov, K.A.; Lytvynenko, R.A.; Vitruk, Y.V.; Gryzodub, O.P.; Stakhovsky, E.A.; Kashuba, V.I. (Experimental Oncology, 2017)
Background: Prostate cancer is one of the most common male cancers in Western countries and takes the third place in morbidity
in Ukraine. It is a highly heterogeneous disease. Aim: To analyze relative expression levels of the TGFB1, IL1B, FOS, EFNA5, TAGLN,
PLAU, and EPDR1 genes in malignant and non-malignant prostate tissues. Materials and Methods: Total RNA was isolated from
16 prostate adenomas, 37 prostate adenocarcinomas, and 29 conventionally normal prostate tissues. To analyze relative gene expression
levels the quantitative real-time polymerase chain reaction was performed. Results: The significant alterations in the relative
expression levels were found in all analyzed sample groups for 4 genes: FOS, EFNA5, IL1B, and TGFB1. We have found that FOS and
EFNA5 were more frequently overexpressed in carcinomas with Gleason score ≤ 7, compared with adenomas. On contrary, PLAU
expression levels were decreased more frequently in prostate cancers, compared with conventionally normal tissues. Noteworthy,
we found positive correlation between IL1B expression level and PSA (for patients with slight PSA increase, no more than 20.0 ng/ml).
Conclusion: The EFNA5, FOS, IL1B, PLAU, and TGFB1 genes that showed significant expression alterations in prostate tumors,
compared with conventionally normal prostate tissue, may play role in prostate cancer development and should be further investigated.